Studi Numerik Perbandingan Kinerja dan Medan Aliran Turbin Vortex Gravitasi dengan Tipe Sudu Lengkung Backward dan Forward - Pamuji, Didit Setyo; Nugroho, Harry Laksono; Sugati, Daru (Mechanical Engineering Department - Semarang State Polytechnic, 2021)
The interaction of turbine blades with vortex flow in micro-hydro power plants based on gravity vortex is still not clearly clarified, therefore numerical simulation is a tool to produce flow visualization that helps analyze the performance of experimental results. This study aims to compare the performance of a gravity vortex flow power generator using a conical basin with a inclined backward and inclined forward blade design using a numerical simulation approach. The simulation begins by validating the results of torque performance and visualizing the flow of experimental research conducted by previous researchers, then the simulation settings are used to compare the performance of the inclined backward and inclined forward blade turbine designs with variations in turbine rotation speed of 80, 120, 160 and 180 rpm. The simulation results show that the curved backward blade performance is better than the forward curved blade which is supported by visualizing the free surface flow and static pressure contours on the blade surface.